1997
DOI: 10.1074/jbc.272.42.26464
|View full text |Cite
|
Sign up to set email alerts
|

Zinc-induced Alzheimer's Aβ1–40 Aggregation Is Mediated by Conformational Factors

Abstract: The heterogeneous precipitates of A␤ that accumulate in the brain cortex in Alzheimer's disease possess varying degrees of resistance to resolubilization. We previously found that A␤1-40 is rapidly precipitated in vitro by physiological concentrations of zinc, a neurochemical that is highly abundant in brain compartments where A␤ is most likely to precipitate. We now present evidence that the zinc-induced precipitation of A␤ is mediated by a peptide dimer and favored by conditions that promote ␣-helical and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
260
0
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 320 publications
(275 citation statements)
references
References 52 publications
14
260
0
1
Order By: Relevance
“…Evidences obtained in vitro suggest that zinc may contribute to A␤ aggregation and thus plaque formation (5)(6)(7)(8). The recent demonstration that metal chelation ameliorates A␤ plaque formation in hAPP ϩ mice strongly supports this hypothesis (13).…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Evidences obtained in vitro suggest that zinc may contribute to A␤ aggregation and thus plaque formation (5)(6)(7)(8). The recent demonstration that metal chelation ameliorates A␤ plaque formation in hAPP ϩ mice strongly supports this hypothesis (13).…”
Section: Discussionsupporting
confidence: 57%
“…First, zinc or copper induces the rapid aggregation of synthetic A␤ in an aqueous environment (5,6), likely by binding to histidine residues within A␤ (7,8). Second, concentrations of the transition metals including zinc and copper are elevated in AD brains, more so around plaques (9)(10)(11).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The toxicity of Aβ in cell culture depends upon the peptide binding to copper [2] or iron [39] through generating radical chemistry (Aβ42>Aβ40) [20,31]. Zinc, copper and iron rapidly precipitate Aβ [2,6,13,19], which then becomes resistant to proteolysis [9]. The brain and CSF are protected from fluctuations in plasma metal concentrations by the bloodbrain barrier.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the ectodomain Cu-binding site of APP, A␤ peptide also contains binding sites for Zn and Cu (13)(14)(15). A␤-metal interaction may drive both fibril formation and free radical production (13,(16)(17)(18), findings potentially relevant to AD pathogenesis in vivo, given that metal chelators can resolubilize A␤ aggregates from postmortem AD brain (19). On the other hand, studies of APP processing in cultured cells have revealed stimulation of the ␣-secretase pathway for APP processing by extracellular Cu ions (20).…”
mentioning
confidence: 99%